AB0412 FACTORS THAT AFFECT THE RESPONSE TO TOCILIZUMAB WITH REGARD TO WORK PRODUCTIVITY IN PATIENTS WITH RHEUMATOID ARTHRITIS: A 2-YEAR FOLLOW-UP OF THE FIRST ACT-SC STUDY. (June 2019) - Tanaka, Yoshiya; Kameda, Hideto; Kazuyoshi, Saito; Kaneko, Yuko; Tanaka, Eiichi; Yasuda, Shinsuke; Tamura, Naoto; Fujio, Keishi; Fujii, Takao; Kojima, Toshihisa; Anzai, Tatsuhiko; Fujino, Yoshihisa; et al.
Abstract : Background: Rheumatoid arthritis (RA) is a major cause of work disability, sickness-related absence from work, presenteeism, and loss of productivity. The decrease in work productivity that results from persistent pain, impaired mobility and function, and reduced quality of life (QOL) has important personal, societal, and economic consequences[1]. The efficacy of tocilizumab (TCZ) as monotherapy and in combination with methotrexate for RA is well known. Thus, in this study, we expected TCZ treatment to improve work productivity on the basis of interim results of up to 52 weeks[2]. Objectives: We aimed to evaluate the long-term (104 weeks) control of RA in Japanese paid workers and house workers treated with TCZ and identify factors affecting the response (responder/non-responder) to TCZ in terms of work productivity. Methods: The FIRST ACT-SC Study (UMIN-CTR: UMIN000012306) was a cohort study that assessed the 2-year treatment outcome of TCZ-SC (administered alone or with disease modifying anti rheumatic drugs) in biologics-naive Japanese patients with RA. Logistic regression analysis was performed to determine the factors contributing to treatment response in terms of activity impairment (AI) in the WPAI questionnaire, which is an index for the evaluation of overall daily life performance. In addition, the associations of these responses to treatment withdrawal rate and QOL were also evaluated. Results: Of the 377 enrolled participants, 357 who were treated with TCZ-SC were included in the analysis. AI was improved from 56.2% at baseline to 22.9% at 104 weeks in the patients who received TCZ. In the single regression analysis, the factors that were statistically significant in the logistic regression analysis were job type (p=0.045), K6 as a measure of psychological distress (p=0.030), Health Assessment Questionnaire-Disability Index (HAQ-DI; p=0.023), and EuroQol five-dimensional descriptive system (EQ-5D) score (p=0.006). In the multiple logistic regression analysis, disease duration, academic background, AI, EQ-5D score, ESR, and CRP level were identified as factors that affected response. The results showed a strong association between the results of the subjective assessments such as the utility value of EQ-5D. At 104 weeks, the mean difference in AI between the EQ-5D scores of <0.6 at baseline and ≥0.6 was significant (−22.94% vs −30.50%; p=0.029). Moreover, the mean difference between the HAQ-DI of <1.5 at baseline and ≥1.5 was significant (−20.46% vs −29.08%; p=0.013). A disease duration of <1 year was also associated with being an AI responder. A significant difference in withdrawal rate was found between the responders and non-responders (27.0% vs. 46.9%; p<0.001), and the 2-year quality-adjusted life-year was also significantly higher in the AI responders. Conclusion: Starting TCZ-SC treatment at an early stage while taking into consideration the subjective self-assessments of the patients may contribute to improvements in labour productivity and QOL, and long-term treatment continuation. References: [1] Best Pract Res Clin Rheumatol. 2015;29(3):495-511. [2] Arthritis Res Ther 2018;20:151. Disclosure of Interests: Yoshiya Tanaka Grant/research support from: Abbvie, Astellas, Bristol-Myers Squibb, Chugai, Daiichi-Sankyo, Eisai, Mitsubishi-Tanabe, MSD, Ono, Taisho-Toyama, Takeda, Speakers bureau: Abbvie, Asahi-kasei, Astellas, Bristol-Myers Squibb, Chugai, Daiichi-Sankyo, Eli Lilly, Eisai, Glaxo-Smithkline, Janssen, Mitsubishi-Tanabe, Novartis, Pfizer Japan Inc, Sanofi, Takeda, UCB, YL Biologics, Hideto Kameda Grant/research support from: AbbVie, Asahi Kasei Pharma, Astellas, Chugai, Eisai, GlaxoSmithKlein, Mitsubishi-Tanabe, Novartis, Consultant for: AbbVie, Eli Lilly, Novartis, Speakers bureau: AbbVie, Asahi Kasei Pharma, Bristol-Myers, Chugai, Eli Lilly, Janssen, Mitsubishi-Tanabe, Novartis, Pfize, SAITO KAZUYOSHI: None declared, Yuko Kaneko Grant/research support from: AbbVie, Eisai, Daiichi Sankyo, Sanofi, Consultant for: Bristol-Myeres Squibb, Eli Lily, Janssen, Speakers bureau: AbbVie, Eisai, Astellas, Chugai Pharmaceutical, UCB, Pfizer, Bristol-Myeres Squibb, Janssen, Tanabe-Mitsubishi, Eiichi Tanaka Consultant for: Abbvie, Ayumi Pharmaceutical, Bristol Myers Squibb, Chugai Pharmaceutical, Eisai Pharmaceutical, Nippon Kayaku, Pfizer, Takeda Pharmaceutical, and UCB Pharma., Shinsuke Yasuda Grant/research support from: Bristol Myers Squibb, MSD, Speakers bureau: Chugai Parmaceutical, Tanabe- Mitsubishi Pharmaceutical, Bristol Myers Squibb, Astellas Pharmaceutical, Naoto Tamura Grant/research support from: Astellas Pharma Inc., Asahi Kasei Pharma, AYUMI Pharmaceutical Co., Chugai Pharmaceutical Co. LTD, Eisai Inc., :Takeda Pharmaceutical Company Ltd., Speakers bureau: Janssen Pharmaceutical K.K., Bristol-Myers Squibb K.K., :Mitsubishi Tanabe Pharma Co., Keishi Fujio Grant/research support from: Astellas, BMS, Daiichi-Sankyo, Mitsubishi Tanabe, Pfizer, Ayumi, Takeda, Chugai, Eisai, Taisho Toyama, UCB, Janssen, Eli Lilly, and NIPPON KAYAKU., Speakers bureau: Astellas, BMS, Daiichi-Sankyo, Mitsubishi Tanabe, Pfizer, Ayumi, Takeda, Chugai, Eisai, Taisho Toyama, UCB, Janssen, Eli Lilly, and NIPPON KAYAKU., Takao Fujii Grant/research support from: Chugai Pharmaceutical, Speakers bureau: Chugai Pharmaceutical, Toshihisa Kojima Grant/research support from: Chugai Pharmaceutical (Investigator Initiated Study), Novartis, Nippon Kayaku, Eli Lilly, Eisai, Speakers bureau: Chugai Pharmaceutical, Takeda Pharmaceutical, Pfizer, Eli Lilly Japan, Bristol Myers Squibb, Ono Pharmaceutical, Daiichi Sankyo, Astelas, UCB, Janssen Pharmaceutical, Tanabe Mitsubishi, Tatsuhiko Anzai Consultant for: Chugai Pharmaceutical, Yoshihisa Fujino: None declared, Shinya Matsuda: None declared, Hitoshi Kohsaka Consultant for: CSL Behring, Speakers bureau: Japan Blood Products Organization, Ayumi Pharmacutical. and Teijin Pharmaceutical.